P.101 A-waves on electrodiagnostic studies in axonal and demyelinating cases of Guillain-Barré Syndrome (GBS). (June 2022) - Reiter-Campeau, S; Gendron, D
Abstract : Background: A-waves are lesser-known late responses of debated clinical significance, seen in routine motor nerve conduction studies (NCS). They are proposed to be a sensitive marker of demyelination and an early finding in acute demyelinating polyradiculoneuropathy (AIDP). We hypothesized that the presence and distribution of A-waves are discriminative markers in differentiating AIDP from axonal variants of Guillain-Barré Syndrome (GBS). Methods: We identified patients diagnosed with demyelinating and axonal forms of GBS at the Montreal Neurological Institute between 2016 and 2021. Clinical and electrophysiological data including raw NCS responses were retrospectively reviewed for 28 AIDP and 9 axonal GBS cases. Results: 20 of 28 AIDP cases had at least one A-wave in non-tibial nerves compared to 2 of 9 axonal cases. Among patients with NCS available within 2 weeks of symptom onset, 13 of 14 AIDP cases had non-tibial A-waves, compared to 0 of 6 axonal cases. Eight of 14 AIDP cases had one or more nerves with multiple A-waves within 2 weeks, compared to 0 of 6 axonal cases. Conclusions: In patients with GBS, the presence of A-waves in non-tibial nerves and of nerves with multiple A-waves are early indicators of the demyelinating variant. Early identification of GBS subtype is valuable for prognostication.